Структура символу як виражальний чинник сакральності в храмобудуванні - Гнідець, Р. Б.; Hnidets, R. (Видавництво Львівської політехніки, 2019)
У статті зроблено спробу розкрити структуру символу у його образі та геометричній формі як вираження сакральної сутності у храмобудуванні. Вона виявляється через ідею-образ, функціонально-змістове наповнення та певне знаково-символьне проявлення у просторі храмових обсягів святині. Оскільки символ у своєму практичному застосуванні виховує у будівничого чутливість до формальної досконалості, гармонії та естетики змісту і сакральної заангажованості, то саме у знаково-символьному вираженні виявляється сакральна сутність храмових будівель.

This article to make the attempt to exposed the symbol structure in its appearance and geometrical form as to expressed the sacral essence in the temple construction. This structure to manifests through the appearance-idea, the functionary-content to fill up and the sure symbol-sign that is show in the space of temple volume in sacred building. The significance manifests itself by the certain feature of the temple buildings, which in their imaginative expression symbolize the sacral essence of the God Temple that is show in some sacral forms-symbols. The place of the temple disposal points out the certain space of placing and manifestation of the sacral essence- “hierophany” as an integral feature and property of this space. Exactly hierophany realizes the sanctification of this place through the imaginative and symbolic structure of the temple building and its immediate influence on the surrounding environment and town building. Every temple and its space contain the tree-measurable cross, as if the space narrows and symbolize the whole universe filled with God. This spatial cross has the shoulders, which are turned to the six space directions and together with the “middle-center” form the seven-point planning of the space / As this “middle-center” is God Jesus Christ that is God himself creates all the sacral space. The space which to create of the exsternal and inner essence of sacral building as to taken the filling and expression through the definite symbolical essences, whose to incarnate by means of defferent to signifies components, which to create and fill up of this space. The organization of architectural space, its his structuring to take the determinate as the primary basis of the architectural composition on the any of level in the system of surroundings environment. The artistic conception-image whose to incarnated in this transfigurative architecture space as to conversion of him to the artistic space. About of the sacral architecture of temple building that to Sacrum as an incarnate conceptionimage create of this sacral space- the place to manifest itself of the mysterious and sacred. Form creation in the architecture creative work to most of all depend upon from that social, world outlook and ideological substance, which to fill up the form of him expression. Its undoubtedly to touch of the architecture of temple building which to the form creation of structure its to accumulated in the temple space the spirit-social source and its society- significant part of him image-sign to be presence of Sacrum. By the since symbol in yours practical use to bring up in builder to sensitivity to the formal perfection, harmony and aesthetics of the content and sacral apprehension to exactly in the symbol-sign express to be manifestation the sacral essence of temple buildings. Every place, which is sacrificed and fixed with the temple building, becomes its symbolical and imaginative center that accumulates the incomprehensible potential of the Heaven Gifts, which show themselves in these buildings.
The symbolic structure as an expression factor to the sacrality of temple construction
Keywords: знак; символ; ідея-образ; форма; формотворення; храмобудування; гармонія; естетика та досконалість; сакральний; іерофанія; sign; symbol; appearance-idea; form; form creation; temple building; harmony; aesthetics; perfection; sacral; hierophany; 726.69